Clay minerals from the Arkitsa fault gouge zone, in Central Greece, and implications for fluid flow - Papoulis, D.; Romiou, D.; Kokkalas, S.; Lampropoulou, P. (Bulletin of the Geological Society of Greece, 2013)
Clay minerals in shallow fault rocks are increasingly recognized as key to the mechanical and seismogenic behavior of faults and fluid flow circulation within the fault core and the surrounding damage zone. We therefore studied faultgouge mineralogy from samples derived from the ENE-trending Arkitsa fault zone, in east-central Greece, in order to testify if the fault is acting as a channel for fluid flow and whether the conditions that characterize the flow can be identified. Clay-gouge samples were collected within the fault core zone, as well as in the broader fault damage area. Consequently, the samples were analyzed by X-Ray Diffraction, SEM and Electron microprobe analyses. The minerals that were identified within the centre of the fault zone are: Montmorillonite, corrensite, illite, micro-calcite, dolomite, quartz, plagioclase and K-feldspars. The absence of corrensite, a clay mineral usually formed in hydrothermal conditions, in the samples from the broader fault damage area indicates that the circulation of hydrothermal fluids is mostly confined within and around the fault core zone. The assemblages within the fault gouge zone and especially the presence of corrensite, combined with the absence of laumontite, indicate hydrothermal alteration at neutral to alkaline conditions and a temperature range at about 100-150 oC.